E3 Siah ubiquitin ligase regulates dichotomous spermatogenesis in Sitotroga cerealella - Shah, Sakhawat; Shi, Chun-Mei; Elgizawy, Karam Khamis; Yan, Wen-Han; Wu, Gang; Wang, Xiao-Ping; Yang, Feng-Lian (Frontiers in Cell and Developmental Biology, 2025)
Spermatogenesis in Lepidoptera holds significant importance due to its unique process of dichotomous spermatogenesis, yielding eupyrene and apyrene spermatozoa through a complex molecular mechanism. While E3 ubiquitin ligases are known to play vital roles in spermatogenesis across various processes, their functions in dichotomous spermatogenesis remain less known. We utilized the RNAi, biochemical and microscopic procedures to unravel the function of ScE3 Siah in dichotomous spermatogenesis of adult Sitotroga cerealella. In S. cerealella E3 ligase Siah predominantly expressed in adult tissues. Knockdown of ScE3 Siah leads to disruptions in testes and sperm morphology, affecting the structure of eupyrene and apyrene sperm bundles and causing defective ultrastructure in eupyrene sperm. This disruption results in a reduction in the number of dichotomous sperms and significantly reduces their motility. Moreover, ScE3 Siah knockdown inhibits the transfer and motility of dichotomous sperm, impacting spermatophore formation in females and ultimately reducing egg production. Understanding the role of ScE3 Siah is not only crucial for comprehending the complex processes involved in dichotomous spermatogenesis and fertilization but also provides an avenue for sustainable pest control management.